Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; M. Le Corre, Vincent; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Royal Society of Chemistry (RSC), 2024)
Fully printed carbon-based flexible perovskite module with an efficiency of 11.6%. Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm 2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
Acknowledgements: The Solar Factory of the Future (SFF) as part of the Energy Campus Nürnberg (EnCN) is acknowledged, which is supported by the Bavarian State Government (FKZ 20.2-3410.5-4-5). Part of this work has been supported by the Helmholtz Association in the framework of the innovation platform “Solar TAP”. T. D. acknowledges the financial support from Deutsche Forschungsgemeinschaft (DFG) via the Perovskite SPP2196 program (project no. 506698391). L. D. gratefully acknowledges funding of the Erlangen Graduate School in Advanced Optical Technologies (SAOT) by the Bavarian State Ministry for Science and Art. L. D. acknowledges Sven Boelke and Ivana Mrsic for XPS measurements. S. Q. and C. L. are grateful for the support from the China Scholarship Council (CSC). J. G. C. gratefully acknowledges the Deutscher Akademischer Austauschdienst (DAAD) for the granting of a doctoral scholarship. F. U. K. thanks the Jardine Foundation and Cambridge Trust for a doctoral scholarship. C. D. acknowledges European Union’s Horizon 2020 research and innovation program (823717–ESTEEM3). F. Y. acknowledges the financial support from the National Natural Science Foundation of China (Grant No. 52102287), Natural Science Foundation of Jiangsu Province (Grant No. BK20210731) and the Natural Science Foundation of the Jiangsu Higher Education Institutions of China (21KJD150003).
Keywords: 40 Engineering; 4016 Materials Engineering; 34 Chemical Sciences; 3406 Physical Chemistry